The role of forging during inertia friction welding of nickel-base superalloy RR1000 (2011)
The dissolution response of y’ phase to thermal and mechanical effects in an inertia friction welded turbine disk nickel base superalloy RR1000 has been investigated. The thermo-chemical affected zone (TMAZ) and heat affected zone (HAZ) microstructures around welds in a commercial PM nickel-based RR1000 superalloy were simulated using a Gleeble thermo-chemical simulation system. Detailed microstructures examination of the simulated TMAZ and HAZ and those present in actual inertial friction welded specimens showed that y’ particles persisted during heating to the welding temperatures, where they reacted in the surrounding y matrix producing liquid film by a eutectic- type reaction. However, it was observed that the compressive strain during the forging stage of welding significantly enhanced resistance to weld liquation cracking of the alloy by strain-assisted rapid isothermal re-solidification of the constitutional liquation products within 150µm of the bond line.